Semiconductor technologies for 5G implementation at millimeter wave frequencies – Design challenges and current state of work - Juneja, Sagar; Pratap, Rajendra; Sharma, Rajnish (Engineering science and technology, an international journal, 2021)
Almost all cellular mobile communications of today take place in sub 3 GHz band that has now become too crowded to support future demands of increasing mobile data traffic. Therefore a new paradigm has been explored for designing next generation cellular communication system (i.e. 5G) using 28 GHz and 39 GHz millimeter wave (mmW) frequency bands. In 2016 Federal Communications Commission (FCC) allocated licensed spectrum of 3.85 GHz in these mmW bands for 5G implementation. There are many unique challenges faced while working with semiconductor technologies at mmW frequencies that are discussed in this paper along with the opportunities and current state of the art in the field. The paper systematically presents propagation related issues of mmW frequencies, effects of modern VLSI technologies in designing mmW circuits, role of passive components and their design issues, and modeling related issues in CMOS technology. The paper uses holistic approach to cover almost all aspects that are important to take into account while working at mmW frequencies for the design of semiconductor circuits for 5G applications.